2008
DOI: 10.1158/1078-0432.ccr-07-4151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketoconazole on the Pharmacokinetics and Pharmacodynamics of Ixabepilone: A First in Class Epothilone B Analogue in Late-Phase Clinical Development

Abstract: Purpose: To determine if ixabepilone is a substrate for cytochrome P450 3A4 (CYP3A4) and if its metabolism by this cytochrome is clinically important, we did a clinical drug interaction study in humans using ketoconazole as an inhibitor of CYP3A4. Experimental Design: Human microsomes were used to determine the cytochrome P450 enzyme(s) involved in the metabolism of ixabepilone. Computational docking (CYP3A4) studies were done for epothilone B and ixabepilone. A follow-up clinical study was done in patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Together with docetaxel, paclitaxel forms the drug category of the taxanes. Taxanes, as well as recently marketed epothilone classes (Goel et al, 2008), stop cell division by inhibition of the microtubule function through stabilizing GDP-bound tubulin in the microtubule. Paclitaxel and docetaxel are administered to patients intravenously because of their poor oral bioavailability.…”
Section: -Tert-butyl-3-n-tert-butyloxycarbonyl-4-deacetyl-3-dephenylmentioning
confidence: 99%
“…Together with docetaxel, paclitaxel forms the drug category of the taxanes. Taxanes, as well as recently marketed epothilone classes (Goel et al, 2008), stop cell division by inhibition of the microtubule function through stabilizing GDP-bound tubulin in the microtubule. Paclitaxel and docetaxel are administered to patients intravenously because of their poor oral bioavailability.…”
Section: -Tert-butyl-3-n-tert-butyloxycarbonyl-4-deacetyl-3-dephenylmentioning
confidence: 99%
“…In humans, co-administration of ketoconazole with ixabepilone increased plasma AUC 0 −∞ (total drug exposure in the plasma) by 79% with a small increase in C p max. In this dose ranging study, the maximum tolerated dose was decreased from 30 mg/m 2 in patients with normal hepatic function to 25 mg/m 2 in the presence of ketoconazole with dose-limiting toxicities of fatigue, neutropenia, mucositis, diarrhea, and febrile neutropenia (Goel et al 2008). In vitro studies indicate that patupilone is a weak inhibitor of CYP2C9, but a phase I study with warfarin did not show signifi cant drug-drug interaction .…”
Section: Pharmacokineticsmentioning
confidence: 96%
“…Therefore liver dysfunction may affect clearance of the active drug. There are interpatient variabilities in drug disposition, especially with ixabepilone which is a substrate of cytochrome CYP3A4 (Goel et al 2008). Incubation of ixabepilone in human liver microsomes with different cytochrome inhibitors demonstrated that metabolism of ixabepilone was inhibited by 90% with a potent CYP3A4 inhibitor (ketoconazole).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Ixabepilone is extensively metabolized in the liver via the cytochrome P-450 CYP3A4 isoenzyme [26], and exposure to the drug is greater in patients with pre-existing hepatic impairment, as is common with patients with metastases to the liver, often reflected by significant elevations in liver transaminases (aspartate transaminase [AST] or alanine transaminase [ALT]) or bilirubin [17]. For example, ixabepilone exposure was 22%, 30%, and 83% greater in patients with bilirubin levels Ͼ1ϫ to 1.5ϫ the upper limit of the normal range (ULN), Ͼ1.5ϫ to 3ϫ the ULN, and Ͼ3ϫ the ULN, respectively.…”
Section: Preventing Adverse Eventsmentioning
confidence: 99%